If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3a + -1 = 7 Reorder the terms: -1 + -3a = 7 Solving -1 + -3a = 7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3a = 7 + 1 Combine like terms: -1 + 1 = 0 0 + -3a = 7 + 1 -3a = 7 + 1 Combine like terms: 7 + 1 = 8 -3a = 8 Divide each side by '-3'. a = -2.666666667 Simplifying a = -2.666666667
| 3x+20=x+100 | | Z^2+10z+12=0 | | x+(2x-4)=32 | | Z^2+10z+10=0 | | 3x-4=8+2x | | (x^3+x)(2x^2-3x-2)=0 | | h^2+5h+6=0 | | 6(t-7)+2(5t+3)=15(t-2)-2 | | 2b+3r=16 | | 7x+18+2x=180 | | -80x(x)=162 | | 6.8(x-2)=-0.2x+35.4 | | 12g=16 | | (12x-15)(12x-21)x=945 | | (6-z)(3z+8)=0 | | 3x+7+2x+17=90 | | -4(2x+8)=3(4-x) | | 9(y+7)=6+8y | | 5-2x=4x+7 | | tan(4x+3)=3 | | 2y-7=3y-6 | | d+1=w | | 3a-(a-1)=4a+5 | | 2.7y=43.2 | | 4(x+12)=4x+48 | | X^2+9y^2=25 | | .25=.6x+.7 | | 6-3(x+10)=3 | | .4x-2=.2x+5 | | (7y^2-8y)+(9y^2-y)= | | 5x+3(-5x-6)-7=82 | | 5.6=0.8x |